2018
DOI: 10.1021/acs.inorgchem.8b00314
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Photoelimination from SbV Dihalide Corroles

Abstract: Main-group p-block metals are ideally suited for mediating two-electron reactions because they cycle between M and M redox states, as the one-electron state is thermodynamically unstable. Here, we report the synthesis and structure of an Sb corrole and its SbX (X = Cl, Br) congeners. Sb sits above the corrole ring, whereas Sb resides in the corrole centroid. Electrochemistry suggests interconversion between the Sb and SbX species. TD-DFT calculations indicate a HOMO → LUMO+2 parentage for excited states in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 80 publications
(145 reference statements)
6
34
0
Order By: Relevance
“…We reported that [( o ‐dppp) 2 Cl 3 Sb V ]Pd II Cl 2 ( B , o ‐dppp= o ‐(Ph 2 P)C 6 H 4 ) (Figure 1) undergoes a clean photoreductive chlorine elimination reaction, which produces [( o ‐dppp) 2 Cl 2 Sb IV ]Pd I Cl, thus suggesting that antimony can support the photoreductive elimination of chlorine [7] . Nocera confirmed this possibility by describing an antimony(V)‐corrole dihalide C (Figure 1), which can also be reduced into the corresponding antimony(III)‐corrole by irradiation [8] . With the view of broadening the type of elements that support this photoreductive chemistry, we put forth the hypothesis that group 14 elements with accessible II/IV oxidation states may also be prone to photoreduction via halogen evolution.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We reported that [( o ‐dppp) 2 Cl 3 Sb V ]Pd II Cl 2 ( B , o ‐dppp= o ‐(Ph 2 P)C 6 H 4 ) (Figure 1) undergoes a clean photoreductive chlorine elimination reaction, which produces [( o ‐dppp) 2 Cl 2 Sb IV ]Pd I Cl, thus suggesting that antimony can support the photoreductive elimination of chlorine [7] . Nocera confirmed this possibility by describing an antimony(V)‐corrole dihalide C (Figure 1), which can also be reduced into the corresponding antimony(III)‐corrole by irradiation [8] . With the view of broadening the type of elements that support this photoreductive chemistry, we put forth the hypothesis that group 14 elements with accessible II/IV oxidation states may also be prone to photoreduction via halogen evolution.…”
Section: Introductionmentioning
confidence: 92%
“…[7] Nocera confirmed this possibility by describing an antimony(V)corrole dihalide C (Figure 1), which can also be reduced into the corresponding antimony(III)-corrole by irradiation. [8] With the view of broadening the type of elements that support this photoreductive chemistry,w ep ut forth the hypothesis that group 14 elements with accessible II/IV oxidation states may also be prone to photoreduction via halogen evolution. To explore this possibility and elaborating on our prior investigation of complexes of type B, [7] we have now decided to investigate platinum-germanium complexes with ad inuclear core designed to support the coveted lightdriven elimination process.…”
Section: Introductionmentioning
confidence: 99%
“…edox reactions are important chemical and biochemical processes that occur in nature and a range of synthetic compounds of interest for catalysis and energy transfer and storage. Most of these reactions involve transition metal complexes, however, recent emphasis has been placed on main group inorganic compounds due to their lightweight and more abundant nature [1][2][3][4][5][6] . In this context, tellurophene, a telluriumcontaining five-membered aromatic ring 7,8 , is of particular interest given that its π-delocalized nature resembles more traditional aromatic heterocycles and that it incorporates a metalloid that is capable of several stable oxidation states 9-11 . In the last decade, the incorporation of the tellurophene-motif into π-extended molecules and polymers has been recognized as a promising design for electronic devices, such as thin film transistors, light emitters, photovoltaics, and thermoelectrics [12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…The polystyrene itself is prone to photodegradation, but much more slowly than the indicators [ 50 ]. In theory, violet excitation of the IrTFPP-CO-Cl could generate chloride radicals that would decompose the metalloporphyrin [ 54 ]. In addition, also the release of the CO ligand could lead to a less stable five-coordinate complex; thus, both effects contribute to the lower stability of the Ir(III) complex.…”
Section: Resultsmentioning
confidence: 99%